Does The Banking Information System Affect Customer Satisfaction and Loyalty? - Defi Insani Saibil (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
This research examines customer satisfaction and loyalty in Islamic banking in the use of internet banking. The research was conducted based on the increase in e-banking users in Islamic banking in Indonesia. E-banking is one of the banking information system services needed today. The research method was carried out using the method of Structural Equation Modeling (SEM) through AMOS and SPSS software. Meanwhile, data collection is carried out through an online survey via a google form. The online survey found 154 respondents of which 27% were from Central Java Province and 47% from the Special Region of Yogyakarta with simple random analysis sample analysis. This study shows that internet banking adoption has a significant effect on customers in Islamic banking, while satisfaction is very large in mediating the relationship between internet banking use and customer loyalty in Islamic banking. Theoretically, this study implies that the banking information system, especially in internet banking, plays an important role in providing service and satisfaction and has a significant effect on customer loyalty.